Prevalence of pain and relative diagnostic performance of screening tools for neuropathic pain in cancer patients: A cross‐sectional study. (30th September 2014) - Pérez, C.; Sánchez‐Martínez, N.; Ballesteros, A.; Blanco, T.; Collazo, A.; González, F.; Villoria, J.
Abstract Background Neuropathic pain can be overlooked in cancer patients. The advent of screening tools can help in recognizing it. However, little is known about their relative diagnostic performance and factors that affect it. This study evaluated the prevalence of neuropathic pain using several diagnostic strategies in cancer patients undergoing chemotherapy. Methods Patients attending the Oncology Unit of the investigators' site to continue their chemotherapy schedule were systematically screened for this cross‐sectional study. Before starting chemotherapy drugs, pain specialists made a clinical diagnosis of neuropathic pain (either disease related, treatment related or comorbid) and medical oncologists administered three validated screening tools. Their relative diagnostic performance and the impact of some pain features on it were analysed using multivariate statistical methods. Results From a total of 358 patients, 194 (54.2%) suffered from pain and 73 (20.4%) had a clinical diagnosis of pure neuropathic or mixed pain. Among the screening tools, the Leeds Assessment of Neuropathic Symptoms and Signs (LANSS) was more specific (93.4%), although less sensitive (68.1%) than the Douleur Neuropathique in 4 Questions (DN4) (sensitivity: 87.5%, specificity: 88.4%). Interestingly, the specificities of these two instruments did not differ in patients with mild pain, while the DN4 remained to be more sensitive than the LANSS regardless of pain severity. Conclusions Neuropathic pain is common in cancer patients undergoing chemotherapy. The DN4 might be of great help for the early detection of patients at risk because of incipient chemotherapy‐related neuropathies and the LANSS to rule out neuropathic pain in patients with complex pain conditions.